2021
DOI: 10.1242/dev.191700
|View full text |Cite
|
Sign up to set email alerts
|

Protein manipulation using single copies of short peptide tags in cultured cells and in Drosophila melanogaster

Abstract: Cellular development and function rely on highly dynamic molecular interactions among proteins distributed in all cell compartments. Analysis of these interactions has been one of the main topics in cellular and developmental research and has been mostly achieved by the manipulation of proteins of interest (POIs) at the genetic level. Although genetic strategies significantly contributed to our current understanding, targeting specific interactions of POIs in a time- and space-controlled manner or analyzing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 103 publications
(170 reference statements)
0
20
0
Order By: Relevance
“…Recently, small, high affinity protein binders such as nanobodies, single-chain variable fragments (scFvs), Designed Ankyrin Repeat Proteins (DARPins) and others have emerged as versatile tools to fill this gap. By fusing these protein binders to well-characterized protein domains and expressing the fusion proteins in vivo, protein function can be directly manipulated in a predicted manner [1][2][3][4][5] . For example, when a protein functions with multiple parameters, protein binder tools targeting each or a subset of these parameters could help to dissect the requirement of each parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, small, high affinity protein binders such as nanobodies, single-chain variable fragments (scFvs), Designed Ankyrin Repeat Proteins (DARPins) and others have emerged as versatile tools to fill this gap. By fusing these protein binders to well-characterized protein domains and expressing the fusion proteins in vivo, protein function can be directly manipulated in a predicted manner [1][2][3][4][5] . For example, when a protein functions with multiple parameters, protein binder tools targeting each or a subset of these parameters could help to dissect the requirement of each parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The moon tag was used along with an orthogonal epitope recognition pair based on an scFv antibody (named "sun tag") to demonstrate a high degree of stochasticity and variation in translation kinetics in live cells (221). Both the moon tag and the alfa tag system can be used to deliver a nanobody-fluorescent protein fusion to a subcellular site of choice (nucleus, mitochondria, cell membrane) when the nanobodies carry the appropriate targeting signals (223). The orthogonality of the moon tag and alfa tag suggests the potential for multiplexing (223).…”
Section: Epitope Tagsmentioning
confidence: 99%
“…Both the moon tag and the alfa tag system can be used to deliver a nanobody-fluorescent protein fusion to a subcellular site of choice (nucleus, mitochondria, cell membrane) when the nanobodies carry the appropriate targeting signals (223). The orthogonality of the moon tag and alfa tag suggests the potential for multiplexing (223). The VHH05-6E pair can also efficiently redirect subcellular protein localization.…”
Section: Epitope Tagsmentioning
confidence: 99%
“…Several nanobodies that recognize small epitope tags have been isolated, including tags known as BC2-tag, EPEA-tag, MoonTag, and ALFA-tag (Traenkle et al, 2015; De Genst et al, 2010 ; Boersma et al, 2019; Tanenbaum et al, 2014; Götzke et al, 2019 ; Cheloha et al, 2020). Some of these have been used to visualize and manipulate tagged proteins by changing their abundance or localization using tag- targeting nanobodies in mammalian cells (Zhao et al, 2019; Vigano et al, 2021). The recently developed ALFA nanobody (NbALFA) recognizes a short peptide of 13 amino acids and provides a system useful for immunoblotting, protein purification, and imaging (fixed or live cells) ( Götzke et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed ALFA nanobody (NbALFA) recognizes a short peptide of 13 amino acids and provides a system useful for immunoblotting, protein purification, and imaging (fixed or live cells) ( Götzke et al, 2019 ). In addition, it has been recently reported that HA frankenbody, a single-chain variable fragment engineered from anti- HA antibody, can be used for live imaging and protein degradation in vivo in Drosophila (Vigano et al, 2021). However, to the best of our knowledge, short linear epitope tag-specific nanobodies have yet to be applied for use in vivo in Drosophila or other multicellular organisms.…”
Section: Introductionmentioning
confidence: 99%